The Role of the Game of Balanced Nutrition Ladder Snake in Influencing Changes in Knowledge and Attitudes of Children in Muhammadiyah Tanjung Morawa Elementary School - Oslida Martony (International Journal of Science and Society, 2019)
This study aims to determine the effect of the educational game of balanced nutrition ladder snakes on changes in knowledge and attitudes and actions in elementary school children in Muhammadyah school, Tanjung Morawa district. This type of research is a Quasi-Experimental study (quasi-experimental design) with the design of One Group Pretest- Posttest. The sample in this study was 75 elementary school children Muhammadiyah Kec. Tanjung Morawa. Data was collected using a questionnaire that was filled in by the respondent himself. If the data is normally distributed then the type of test used is the dependent T-test (in pairs). If the data is not normally distributed then the test used is the ranking test. The statistical test results obtained p-value = 0,000 < 0.05, which shows that the influence of snake ladder education game balanced nutrition to changes in knowledge and attitudes in school children. The conclusion in this study is the influence of the educational game of balanced nutrition ladder snakes on changes in knowledge and attitudes in school children.